Community pharmacists' attitudes toward practice-based research and their perceived utilization of scientific evidence. - Eman Alefishat (PLoS ONE, 2022)
Background Enhancing the contribution of practicing pharmacists into scientific evidence via practice-based research (PBR) is crucial in maintaining high-quality clinical practice and healthcare delivery. Involving community pharmacists in PBR can potentially can also help break barriers to the utilization of the current best evidence in everyday pharmacy practice. The impact of pharmacists' attitude towards PBR on their utilization of current best evidence in pharmacy practice is understudied. Objectives The aim of the study was to investigate the impact of community pharmacists' attitudes toward PBR on their utilization of current best evidence, barriers for conducting PBR in clinical practice were also investigated. Methods In this cross-sectional study, 169 community pharmacists working across Jordan filled a questionnaire to assess their attitudes towards PBR, barriers to PBR, and their utilization of the current best evidence in clinical practice. Results Pharmacists in this study showed a positive attitude toward PBR (attitude mean score >3.5). A positive attitude towards PBR was associated with high utilization of the best current scientific evidence. We also investigated several barriers to PBR and their association with utilization those included; the lack of perceived benefits, lack of institutional support, and lack of self-engagements of community pharmacists to PBR. The lack of perceived benefit was found to be negatively associated with pharmacists' utilization of the current best scientific evidence. Conclusion In this study, pharmacists' utilization of current best evidence was found to be significantly impacted by their attitude toward PBR. The current study findings highlight the importance of supporting, promoting, and facilitating PBR among community pharmacists which can potentially enhance their utilization of the current best evidence in their everyday pharmacy practice.